WORKING ON DEVELOPMENT OF PERFORMANCE TECHNIQUE ON GIJJAK KABUS BASS INSTRUMENT - Choriyev Bekzod Bahrom o‘g‘li (Journal Park Publishing, 2024)
This article contains short but necessary information about the topic "Working on the development of performance technique on the bass instrument of gijjak kabus bas".
Keywords: Nightmare bass, technique, instrumental music, detache, tenuto, legato, portato, martele, marcato, accent, staccato, viotti, spiccato, spicato volant, sautille, ricochet, tremolo, col legno.